1977
DOI: 10.1001/archsurg.1977.01370060017002
|View full text |Cite
|
Sign up to set email alerts
|

Primary Small Bowel Volvulus

Abstract: A t laparotomy, 2 L of ascites was suctioned out and the entire intraperitoneal small bowel was found to be ischemic. Volvulus of the smallbowel mesentery was the etiologic factor (the 71-yearold patient had a congenital malrotation). The smallbowel mesentery was detorsed in a counterclockwise fashion, resulting in an immediate change from ischemic (purple) bowel to a normal appearance with almost immediate restoration of peristalsis. Adhesiolysis was performed on a band connecting a proximal loop of jejunum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
2
3

Year Published

1990
1990
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 5 publications
3
62
2
3
Order By: Relevance
“…Cases of SBV involving a jejunal diverticulum have been reported more often in Asia than in the West. [5][6][7] The incidence of diverticulum of the jejunum may be high in Asia. It is reported that small-bowel diverticulum in older people is an independent risk factor for SBV, 8 and large diverticulum of the small bowel, in particular, might play a contributing role in the occurrence of SBV in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of SBV involving a jejunal diverticulum have been reported more often in Asia than in the West. [5][6][7] The incidence of diverticulum of the jejunum may be high in Asia. It is reported that small-bowel diverticulum in older people is an independent risk factor for SBV, 8 and large diverticulum of the small bowel, in particular, might play a contributing role in the occurrence of SBV in adults.…”
Section: Discussionmentioning
confidence: 99%
“…World-wide the prevalence has ranged from 5% in the United States to 51% in India [2, 3]. It is uncommon in most affluent countries but is one of the most common acute surgical problems encountered among certain African, Asian and Middle Eastern nations [4]where in some series the majority of cases present as idiopathic ones [5]and where it can reach 13% of all patients with small bowel obstruction [6]. …”
Section: Discussionmentioning
confidence: 99%
“…1 Reports of primary volvulus of the small intestine are rare in Western Europe and the United States, but this condition is one of the more common surgical emergencies in Central Africa, India, and the Middle East. 1-3 Duke and Yar 1 suggested that the high incidence in Afghanistan was related to abrupt changes in dietary intake at Ramadan (the yearly festival when Muslims fast from sunrise to sunset for 1 month).…”
Section: Discussionmentioning
confidence: 99%
“…1-3 Duke and Yar 1 suggested that the high incidence in Afghanistan was related to abrupt changes in dietary intake at Ramadan (the yearly festival when Muslims fast from sunrise to sunset for 1 month). 1 They suggested that the absence of food during daylight hours and the consumption of a single, large, high-fiber meal at night was related to the high incidence of this disease during the festival. In Japan, reports of primary volvulus of the small intestine are very rare; in our search of the Japanese literature, we found only 15 reported cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation